Start-up Costs and Pecuniary Externalities as Barriers to Economic Development - Antonio Ciccone; Kiminori Matsuyama (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
One critical aspect of economic development is that productivity growth and a rising standard of living are realized through more roundabout methods of production and increasing specialization of intermediate inputs and producer services. We use an extended version of the Judd-Grossman-Helpman model of dynamic monopolistic competition to show that an economy that inherits a small range of specialized uinputs can be trapped into a lower stage of development. The limited availability of specilized inputs forces the final goods producers to use a labor intensive technology, which in turns implies a small inducement to introduce new intermediate products. The start-up costs, which make the intermediate goods producers subject to dynamic increasing returns, and pecuniary externalities that result from the facto rsubstitution in the final goods sector, play essential roles in the model.
Keywords: L16; O11; O31; 330; Differentiated intermediate inputs; the Hicks-Allen Complementarity; Increasing returns to to specialization; Roundabout Production; Multiple steady states; Multiple equilibria; Development traps and takes-off; Endogenous growth